2008
DOI: 10.1063/1.2946433
|View full text |Cite
|
Sign up to set email alerts
|

Collisionality dependence of the quasilinear particle flux due to microinstabilities

Abstract: The collisionality dependence of the quasilinear particle flux due to the ion temperature gradient (ITG) and trapped electron mode (TEM) instabilities is studied, by including electron collisions modeled by a pitch-angle scattering collision operator in the gyrokinetic equation. The inward transport due to ITG-modes is mainly caused by magnetic curvature and thermodiffusion and can be reversed as electron collisions are introduced, if the plasma is far from marginal stability. However, if the plasma is close t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 13 publications
3
16
1
Order By: Relevance
“…For the GA standard case, this expression gives a/L nzc = 0.58 for Z = 6 and a/L nzc = 0.67 for Z = 10, which are in excellent agreement with the values that are obtained by keeping all the terms in the expression for the impurity flux (here we usedγ = 1.2 and ω n 0 = 0.2). Equation (21) shows that for higher impurity temperature gradient or higher k θ ρ s the zero-flux impurity density gradient is lower, a trend which is in good agreement with our numerical results.…”
Section: B A/l Nz -Scalingsupporting
confidence: 81%
See 3 more Smart Citations
“…For the GA standard case, this expression gives a/L nzc = 0.58 for Z = 6 and a/L nzc = 0.67 for Z = 10, which are in excellent agreement with the values that are obtained by keeping all the terms in the expression for the impurity flux (here we usedγ = 1.2 and ω n 0 = 0.2). Equation (21) shows that for higher impurity temperature gradient or higher k θ ρ s the zero-flux impurity density gradient is lower, a trend which is in good agreement with our numerical results.…”
Section: B A/l Nz -Scalingsupporting
confidence: 81%
“…The effect of collisions on the impurity flux only enters through the eigenfrequency, which means that the impurity flux is only very weakly dependent on collisionality. This is in contrast to the very sensitive dependence of the electron particle flux on collisionality, for which in general a sign change from inward to outward is expected at very small collisionalities [1,2,20,21,25].…”
Section: Collisionality Scalingcontrasting
confidence: 40%
See 2 more Smart Citations
“…[6][7][8][9][10] On the theoretical side, it has been shown that the transport fluxes are dependent on the choice of the collision operator. 11 Numerical simulations of ion temperature gradient ͑ITG͒ and trapped electron ͑TE͒ modes have shown that collisions may influence the sign and the magnitude of the quasilinear fluxes driven by these instabilities. 12 Without collisions, the quasilinear particle flux driven by ITG modes is usually inward due to curvature and thermodiffusion.…”
Section: Collisional Model Of Quasilinear Transport Driven By Toroidamentioning
confidence: 99%